Memória, gênero e política : a militância das estudantes da Universidade Federal do Espírito Santo contra a ditadura militar (1969-1972) - Lima, Gabriela Rodrigues de (2017)
The recent emergence of memories referring to the political struggles of resistence to the Military Regime instated in 1964 and remained in force until 1985 reveals the predominance of reports done by men who engajed in political organizations that opossed the autoritharian Estate by then. In a audience promoted by the UFES’ “Comissão da Verdade” (Truth Comission , CV) in the year of 2014 it was notorious the majoritary participation of former male students who told their political experiences in the student moviment. This considered, the objective of this work is to rescue the relates and memories of the political experience lived by the women that were involved in the fight for resistence organizaed by the student movement that took place in this University, offering to them the hearing for their narratives and developing , from that, questions that referres to their political participation and the inequalities of gender revealed in it. The research began with the contact to the oral depositions conceded to the CV UFES and the documentation that came from recently opened archives of the “Assessoria Especial de Segurança e Informação” (Special Advisory to Security and Information, AESE), that existed in the university. The research traces the context of the years between 1968 and 1972, when the political and institutional persecution was most intense. From the description presented based on the documents and depositions, we turn our attention to the analysis of one female student’s life story that fought against the regime in the university, Dr. Laura Coutinho, with the purpose to relate this period’s history with the problem of gender relations in history. The objective of this research is to rescue the women’s memories who lived in the repression and the political organization in dictatorship’s times, and to make notice of the women’s importance in the official history. This effort is just a part of a bigger Project that seeks to criticize the official history , always centred on the males, and the rescue of the women’s history as part of a more just and democratic History.